Rancang Bangun Sistem Informasi Kader Organisasi Forum Pemuda Pelajar Mahasiswa Tangerang (FPPMT) - Rohmat Taufiq; Muhamad A'raf Iskandar; Sofia Ashar (Teknik Informatika Universitas Pamulang, 2021)
In an organization, of course, it cannot be separated from the term cadre or cadre. The strength of an organization is influenced by the cadres in it. If there are militant cadres who have good competence, it is certain that the organization will not experience many obstacles. Therefore, the role of cadres in the organization has a tremendous impact. This study uses interview and observation methods for the data collection process, while in the process of developing the system using the waterfall method which consists of communication with all the elements involved, planning research activities, making models with a unified modeling language (UML) and the last step is making reports. The conclusion of this research is that a Desktop-based application for the cadre data application for the Tangerang Student Youth Forum (FPPMT) has been made. The application is expected to contribute to the research organization.